Obsessive-Compulsive Disorders. Issue 6 (December 2021) - Mathews, Carol
ABSTRACT: PURPOSE OF REVIEW: This article describes the phenomenology and clinical presentation of obsessive-compulsive disorder (OCD), a common but underdiagnosed psychiatric disorder. Guidance for effectively identifying obsessive-compulsive symptoms is provided, and treatment options, including psychotherapy, pharmacologic management, and neuromodulation approaches for treatment-resistant OCD, are discussed. RECENT FINDINGS: OCD affects 2% to 3% of adults worldwide and is associated with substantial individual disability and societal costs. Lack of recognition of common OCD symptom types, in addition to shame and fear of stigma on the part of patients, has created an average delay in diagnosis by almost 10 years and a delay in effective treatment (ie, a treatment gap) of nearly 2 years. Cognitive-behavioral therapy (CBT), specifically a form of CBT that includes a type of behavioral intervention called exposure and response prevention, remains the most effective form of treatment for OCD. If CBT is not effective or not available, pharmacologic treatment with selective serotonin reuptake inhibitors (SSRIs) or clomipramine, a nonselective serotonin reuptake inhibitor, can also be of benefit. Neuromodulation approaches such as deep brain stimulation and transcranial magnetic stimulation are rapidly emerging as effective treatments for OCD, particularly for patients who have not experienced an adequate response to psychotherapy or pharmacologic management. SUMMARY: OCD affects more than one in every 50 adults in the United States but is recognized and adequately treated in fewer than half of those affected. Early intervention and appropriate treatment can substantially reduce OCD symptom severity, improve quality of life, and minimize the functional disability associated with this chronic and often debilitating illness.